2018
DOI: 10.1096/fj.201701529rr
|View full text |Cite
|
Sign up to set email alerts
|

Cre‐dependent AAV vectors for highly targeted expression of disease‐related proteins and neurodegeneration in the substantia nigra

Abstract: Recombinant adeno-associated virus (AAV) vectors are a popular genetic approach in neuroscience because they confer such efficient transgene expression in the brain and spinal cord. A number of studies have used AAV to express pathological disease-related proteins in the dopaminergic neurons of the substantia nigra in situ ( e.g., α-synuclein to model aspects of Parkinson's disease). The neuropathology and neurodegeneration of Parkinson's disease occur in a circumscribed pattern in the brain, and one of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…i) The first and most obvious difference is that we restricted α-synuclein overexpression to DA neurons within the SNc while the other studies relied on non-cell type specific α-synuclein vectors. To our knowledge, there are only two other studies that relied on cell-type specific AAVs to overexpress α-synuclein so far: a study by Grames et al showed that overexpression of wildtype human α-synuclein (using AAV9-EF1α-DIO-hASYN WT ) in the SNc of TH Cre rats did not induce any loss of TH neurons four weeks after injection [14], which is in line with our findings in mice. And we showed previously that overexpression of the disease-associated variant α-synuclein A53T (using AAVDJ-hSyn1-DIO-hASYN A53T ) did not induce significant changes in the number of TH mRNA + neurons in the SNc three months after virus injection in DAT Cre mice [43].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…i) The first and most obvious difference is that we restricted α-synuclein overexpression to DA neurons within the SNc while the other studies relied on non-cell type specific α-synuclein vectors. To our knowledge, there are only two other studies that relied on cell-type specific AAVs to overexpress α-synuclein so far: a study by Grames et al showed that overexpression of wildtype human α-synuclein (using AAV9-EF1α-DIO-hASYN WT ) in the SNc of TH Cre rats did not induce any loss of TH neurons four weeks after injection [14], which is in line with our findings in mice. And we showed previously that overexpression of the disease-associated variant α-synuclein A53T (using AAVDJ-hSyn1-DIO-hASYN A53T ) did not induce significant changes in the number of TH mRNA + neurons in the SNc three months after virus injection in DAT Cre mice [43].…”
Section: Discussionsupporting
confidence: 91%
“…II) We used the human Synapsin 1 (hSyn1) promoter to drive α-synuclein expression, while most other commonly used AAVs for α-synuclein overexpression used very strong promoters such as CBA (ß-actin promoter with enhancer elements from the CMV promoter) or CMV. Use of the latter promoters may lead to even higher α-synuclein expression levels than with the hSyn1 or EF1a promoter [14, 43] and therefore they may be more likely to induce toxicity. Note that there are also reports showing that ‘inert’ proteins like GFP can cause toxicity suggesting that overexpression of any protein may become toxic once a critical threshold is reached [4, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, loss of dopaminergic neurons and neuroinflammation were more severe when AAV‐P301L Tau protein was injected in aged (20 months old) compared to adult (3 months old) rats (Klein, Dayton, Diaczynsky, & Wang, ). A recent study expanded previous work by using rAAV9 to express Cre‐recombinase‐dependent vectors in rats that express Cre under the control of the TH promoter in dopaminergic neurons (Grames et al, ). Delivering vectors with loxP‐flanked inverted (inactive) coding sequences allows the testing of several pathogenic proteins, including P301L Tau, under similar experimental conditions in Cre‐expressing cells that flip the CDS and therefore allow transcription.…”
Section: Aav‐based Ad Mouse Modelsmentioning
confidence: 91%
“…For complex disorders like PA, the identified DEGs are expected to contain a substantial percentage of PA-related genes [92], and a certain number of irrelevant genes may be inevitably selected due to measurement variability. Herein, a comprehensive literature review was performed to investigate the PA relevance of the top-ranked DEGs.…”
Section: Methodsmentioning
confidence: 99%